Healthcare Access of Autistic Language Minorities: The Case of English Official Language Minorities in Quebec, Canada - Amantayev, Nariman; Rao, Sabrina; Nadig, Aparna (Minorités linguistiques et société, 2025)
Abstract English and French are both official languages in Canada. Whereas official language minorities (English speakers in Quebec, French speakers in the rest of Canada) face healthcare barriers and poor health outcomes, autistic individuals and their families also struggle with accessing healthcare. We examined healthcare access at the intersection of these groups: the autistic community, including English minority-language speakers from Quebec, French majority-language speakers from Quebec, and English majority-language speakers from elsewhere in Canada (n = 165). Linguistic minorities reported poorer access to publicly-funded services and lower satisfaction that their language needs were being met than did linguistic majorities. Foreign-born English speakers also experienced poorer access than their Canadian-born counterparts. These preliminary findings suggest that autistic language minorities face known barriers to accessing healthcare, potentially at a higher rate than that experienced by language minorities in general. Résumé L’anglais et le français sont les langues officielles du Canada. Les minorités de langue officielle (anglophones au Québec, francophones hors Québec) font face à des obstacles en matière de santé, tout comme les personnes autistes et leurs familles. Nous avons examiné l’accès aux services de santé à l’intersection de ces groupes : la communauté autiste, incluant des anglophones (minoritaires) et francophones (majoritaires) du Québec, ainsi que des anglophones (majoritaires) du reste du Canada (n = 165). Les minorités linguistiques déclarent un accès plus difficile aux services de santé publics et une moindre satisfaction quant à la prise en compte de leurs besoins linguistiques, comparativement aux majorités linguistiques. Les anglophones nés à l’étranger rapportent également un accès plus difficile que leurs pairs nés au Canada. Ces résultats préliminaires suggèrent que les minorités linguistiques autistes font face à des obstacles connus en matière d’accès aux soins, possiblement à un degré plus élevé.

Les minorités linguistiques du Canada et la santé - Bouchard, Louise; Desmeules, Martin (Politiques de santé, 2013)
Résumé Les minorités de langue officielle (les francophones hors-Québec et les anglophones du Québec) représentent près de 6,4 % de la population canadienne. Bien que le français et l’anglais aient un statut d’égalité juridique selon la Constitution canadienne, il y a lieu de s’interroger sur leur égalité dans le domaine de la santé : les communautés francophones et anglophones du Canada, selon leur statut de minorité ou de majorité, présentent-elles le même profil santé ? Ont-elles accès aux mêmes services de santé et dans les mêmes conditions ? L’objectif de cet article cet article est de rendre compte des enjeux de santé reliés au fait d’appartenir à une minorité linguistique. Nos recherches permettent de mettre en évidence des disparités sociales et de santé qui peuvent être attribuées au fait minoritaire. Dans le contexte canadien des deux langues officielles, une politique de santé équitable devra dorénavant pren dre en considération la situation linguistique minoritaire comme déterminant de la santé. Abstract Official language minorities (Francophones outside of Quebec and Anglophones in Quebec) make up about 6.4% of the Canadian population. Even though the Canadian constitution gives legal equality status to French and English, there is still room to ask if this equality is maintained in the health sector. In other words, do Francophone and Anglophone communities of Canada have the same health profiles regardless of their minority or majority status? Do they have access to the same health services and in the same conditions? The objective of this paper is to identify the health issues associated with belonging to a linguistic minority. Our research allows us to highlight the social and health disparities that can be attributed to belonging to a minority. In the Canadian context, which has two official languages, an equitable health policy will have to take into consideration language as a determinant of health.

Public policy and citizen-based practices that support social and health services for official and co-official language minority communities. An international perspective: What has really been achieved and what are the gaps | Politiques publiques et pratiques citoyennes soutenant les services sociaux et de santé pour les communautés minoritaires de langue officielle et coofficielles. Une perspective internationale : ce qui a été accompli et ce qui reste à faire - Bouchard, Louise; Nyqvist, Fredrica; Mari Mayans, Isidor; van Kemenade, Solange; Maisonneuve, Alexander. R. (Linguistic Minorities and Society / Minorités linguistiques et société, 2021)

Health profile of English-speaking minority communities in Canada [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)

Barrières linguistiques dans l'accès aux soins de santé - Bowen, Sarah (Santé Canada, 2001)

Language barriers in access to health care - Bowen, Sarah (Health Canada, 2001)

Améliorer la santé et le bien-être des Madelinots anglophones. Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Anglophone Magdalen Islanders, 2017)

Availability, accessibility and acceptability of english-language mental health services for the Estrie region’s english-speaking population: Service user and provider perspectives - Charpentier, Claude; Stout, Dale; Benoit, Annie; Poulin, Edith; Philip, Christopher (Journal of Eastern Townships Studies, 2011)
Mental illness affects about 1 in 5 Canadians during their lifetime but only approximately 30% of people needing help actually access mental health ser vices (Gravel, Connolly & Bédard, 2004). This low access rate is worrisome and may not accurately depict the reality as it is lived out by linguistic minorities. The present study documents both the need for and access to English-lan guage mental health services by the Estrie region’s English-speaking minority. Intending to record their needs and access experiences against the backdrop of available English-language mental health services, both users and providers of these services were surveyed in tandem. This novel approach to mental health needs assessment research shows the precarious situation of this minority community (high need/low access to language-congruent mental health ser vices) to be further compromised by misperceptions of service availability.

Portrait des minorités de langue officielle au Canada : les anglophones du Québec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistique Canada, 2010)

Portrait of Official-Language Minorities in Canada: Anglophones in Quebec - Corbeil, Jean-Pierre; Chavez, Brigitte; Pereira, Daniel (Statistics Canada, 2010)

Les minorités prennent la parole : résultats de l'Enquête sur la vitalité des minorités de langue officielle - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistique Canada, 2007)

Minorities speak up: Results of the survey on the vitality ot the Official-Language Minorities - Corbeil, Jean-Pierre; Grenier, Claude; Lafrenière, Sylvie (Statistics Canada, 2007)

English-language Health and Social Services Access in Québec. Comparison 2019-2023 - CROP (Community Health & Social Services Network, 2023)

L’accès en anglais aux services de santé et aux services sociaux au Québec. Version française du rapport comparatif 2023-2019 - CROP (Community Health & Social Services Network, 2024)

Identification des communautés anglophones du Québec : approche populationnelle dans le cadre de l’évaluation des disparités de santé associées à l’infarctus du myocarde - Drouin, Catherine; Courteau, Josiane; Orzanco, Maria Gabriela; Leroux, Denis; Vanasse, Alain (Revue d’études des Cantons-de-l’Est, 2011)
Il existe peu de données probantes permettant d’évaluer les disparités en matière de santé entre les groupes linguistiques au Québec. Ce projet propose une méthode de classification des communautés du Québec en fonction de l’appartenance linguistique de la population ainsi que l’association, basée sur le lieu de résidence des patients, des données médico-administratives et de celles du recensement. Ensuite, des comparaisons entre les groupes linguistiques quant aux traitements et au suivi des cas d’infarctus du myocarde, réalisées à l’aide de tests du Khi carré, permettent d’identifier que la principale disparité se manifeste dans les taux de revascularisation.

« I don’t think that’s the way healthcare for an 85 and an 88-year-old should be done. » L’accès aux services de santé et aux services sociaux des aînés anglophones vivant hors Montréal : état de la situation [thèse de maîtrise, Université de Sherbrooke] - Ethier, Alexandra (Université de Sherbrooke, 2020)
Les aînés anglophones du Québec hors Montréal ont un accès variable aux services de santé et services sociaux (SSSS). C’est pourquoi notre recherche explore l’accès aux SSSS pour les aînés anglophones vivant hors Montréal. Spécifiquement, nous décrivons les facteurs (facilitateurs et barrières) influençant l’accès aux SSSS. Ainsi, nous avons conduit une recherche qualitative de type étude de cas unique imbriquée. Nous avons collecté les données à l’aide d’entretiens semi-dirigés audio-enregistrés, d’un questionnaire sociodémographique et d’un journal de bord. Nous avons transcrit, puis analysé thématiquement les entretiens et avons analysé les données sociodémographiques par statistiques descriptives. Les 10 aînés rencontrés nous ont permis d’identifier 11 facteurs divisés en 6 facilitateurs et 8 barrières influençant l’accès aux SSSS. Les plus signifiants sont la concordance (facilitateur) ou la non-concordance (barrière) de la langue de l’aîné avec le travailleur des SSSS, où la nonconcordance mène à des consentements aux interventions non valides. Également, le facteur présence minoritaire, c’est-à-dire la concentration de la population anglophone, affecte les opportunités sociales des aînés. Ce facteur est un facilitateur lorsque fort et une barrière, lorsque faible. Enfin, des SSSS peu « amis » des aînés anglophones, définis comme un système de SSSS complexe à naviguer lorsque la langue des aînés et leurs caractéristiques personnelles ne sont pas prises en considération, constituent également une barrière. Les résultats de cette recherche informent sur les actions à poser pour faciliter l’accès aux SSSS de ces aînés anglophones et suggèrent des améliorations bénéfiques pour l’ensemble de la population.

L'accessibilité des services sociaux et de santé chez les minorités de langue officielle du Canada et les facteurs influant sur leur accès : une étude de portée - Éthier, Alexandra; Carrier, Annie (Minorités linguistiques et société, 2022)
Les minorités de langue officielle (MLO) du Canada rencontrent des difficultés d’accès aux services sociaux et de santé (SSS). Or, il n’existe aucun portrait exhaustif des services concernés par ces difficultés et des facteurs (facilitateurs et barrières) qui modulent leur accès. Ainsi, le but de cette étude était de décrire l’accessibilité des SSS et d’identifier les facteurs influant sur l’accès aux SSS pour les MLO canadiennes. Une étude de portée dans neuf banques de données combinée à une stratégie élargie a permis d’inclure 74 documents. Les SSS sont généralement insuffisants pour les MLO. De plus, 15 facteurs (8 facilitateurs, 11 barrières) ont été identifiés. Enfin, 26 connexions (une parmi les facilitateurs, 25 parmi les barrières) ont été notées, complexifiant l’accès aux SSS pour les MLO. Intervenir pour favoriser l’accès aux SSS des MLO pourrait être bénéfique à l’ensemble des populations canadiennes, étant donné la présence de barrières communes entre ces groupes. Mots-clés : services sociaux et de santé, minorité anglophone, minorité francophone, facilitateurs, barrières

Strategies to access health and social services for English-speaking older adults in Quebec: A qualitative case study - Ethier, Alexandra; Carrier, Annie (Canadian Social Work Review, 2023)
Considering that French is the dominant language in Quebec, that relatively few francophone providers of health and social services are able to speak English, and that English-speaking older adults (OAs) have low levels of bilingualism, anglophone OAs are more likely than their francophone peers to face language barriers when accessing health and social services. However, little is known about the strategies English-speaking OAs put into place to overcome the difficulties encountered due to language barriers when they access these services. We therefore aimed to document the strategies used by English-speaking OAs when, due to language barriers, they faced difficulties in accessing health and social services. We conducted a qualitative case study with ten English-speaking OAs in the Eastern Townships in Quebec. Through interviews and document reviews, we collected data which we then analyzed thematically. We identified seven strategies used by English-speaking OAs: investigating for health- and access-related information in English, creating their own services, entering the health and social services system offered in French, entering the health and social services system with help from others, putting the responsibility of overcoming the language barrier on the provider, splitting that responsibility, and taking on the responsibility. Our results highlight a potential burden associated with the involvement of the English-speaking community in enabling English-speaking OAs to access health and social services. Keywords: access, health services, social services, official language minority, language barriers, strategies

Seeking social services on the Gaspé coast: A narrative analysis of Anglophones’ experiences of access and care [master's thesis, University of Victoria] - Finlayson, S. (University of Victoria, 2017)
This research addresses the concern that Anglophone populations in the predominantly French speaking Gaspé region of eastern Québec are experiencing high rates of social problems such as poverty and unemployment. Anglophones in this region, as in other rural regions of Québec, have identified facing difficulties related to access to social services, an aspect which further complicates existing social problems. Using a narrative methodology and post structural, feminist and intersectional lenses, this research explores the experiences of English speaking service users in accessing and engaging with social services on the Gaspé coast. This study also explores the boundaries and reproduction of linguistic categories and identity and offers insight into resisting dominant discourses pertaining to linguistic difference in Québec, specifically within the context of social services. The results of this research demonstrate that service users’ experiences were characterised by disproportionately negative effects in regards to service access and delivery such as intensified logistical problems and social work practice related weaknesses. The research also concludes that experiences involved multiple, intersecting problems, which were irreducible to the singular dimension of language. The intersections of language and race, language and class, and language and ability were raised as critical concerns in terms of access to social services on the Gaspé coast. Finally, the encounters between Anglophones and Francophones in the context of health and social services in the region were found to be entangled and inseparable from the historical and ongoing political struggles over language on this territory.

Access to health care services and self-perceived health of canada's official-language minorities [master's thesis, University of Ottawa] - Gagnon-Arpin, Isabelle (University of Ottawa, 2011)

Accès et utilisation des services de santé en langue minoritaire - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (La vie dans une langue officielle minoritaire au Canada, 2014)

Access and use of health care services in the minority language - Gagnon-Arpin, Isabelle; Bouchard, Louise; Leis, Anne; Bélanger, Mathieu (Life within an official language minority in Canada, 2014)

Community involvement of seniors in the Eastern Townships - Gosselin, Chedly; Viens, Caroline (Journal of Eastern Townships Studies, 2006)
This paper explores Anglophone seniors' participation within the community of the Estrie region of Quebec. A healthy relationship between Anglophone and Francophone communities improves access to state health and social services and relieves the social isolation of those living in rural areas. Immigrant migration to the area as well as out-migration of young Anglophones is profoundly affecting the delivery of health and social services as well as changing family, community, nation, culture and what it means to be a citizen.

Frontières linguistiques et culturelles : le cas de l’accessibilité aux services de santé et de services sociaux pour la population anglophone de la région de Québec - Hanrahan, Louis; Cloutier, Annabelle; Walling, Richard (Cahiers de l’ÉDIQ, 2016)

Perceived importance of native language use in service encounters - Holmqvist, Jonas; Van Vaerenbergh, Yves (The Service Industries Journal, 2013)
Despite the importance of interactions in services, the role language plays in services is an under-researched field. This paper outlines for which services language is especially important. Consistent across studies in three countries (Belgium, Canada and Finland), the findings suggest that bilingual consumers find it particularly important to be served in their native language in high-involvement services. Moreover, for high-involvement services, all consumers find it important to be served in their native language. For low-involvement services, elderly consumers are less willing to switch language than young consumers. The importance of native language use did not differ between males and females.

Les services de santé au Canada : une perspective linguistique - Lacroix, Frédéric (L'Action nationale, 2006)

Perceptions des communautés de langue officielle en situation minoritaire : accès aux services de santé dans la langue officielle de son choix. Rapport final - Léger (Santé Canada, 2020)

L'accès aux soins de santé des communautés de langue officielle en situation minoritaire (CLOSM) au Canada : une recension des écrits - Muray, Mwali; Peguero-Rodriguez, G.; Scarlett, Emilie; Perron, Amélie; Chartrand, Julie (Minorités linguistiques et société, 2022)
Cette étude présente une recension des écrits sur les expériences des patients et des prestataires de soins en ce qui concerne les services de santé au Canada offerts aux communautés de langue officielle en situation minoritaire (CLOSM). Mandatée par le Bureau d’appui aux communautés de langue officielle (BACLO), cette recension fait constat des défis et des obstacles qui entravent l’offre de services de santé et l’accès aux soins pour les CLOSM dans la langue officielle de leur choix, et propose des recommandations à l’intention des patients, des professionnels de la santé, des établissements de santé, des différents ordres de gouvernement au Canada et des chercheurs. Cette recension des écrits met en lumière le manque d’exécution systémique des stratégies, afin de faciliter l’accès aux services de santé dans leur langue pour les CLOSM fondées sur des données probantes. Elle s’interroge également sur le fait que peu de stratégies fondées sur des données probantes ont été mises en oeuvre à l’échelle du système malgré des décennies de recherche sur le sujet. Mots-clés : accès aux soins de santé, communautés de langue officielle en situation minoritaire (CLOSM), patients, professionnels de la santé, recension des écrits

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, Brenda, R.; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Accès aux services de santé et aux services sociaux en anglais au Québec. Rapport de données de base 2005-2006 - Pocock, Joanne (Réseau communautaire de santé et de services sociaux, 2006)

English-language health and social services access in Québec. Baseline data report 2015-2016 - Pocock, Joanne (Community Health and Social Services Network, 2016)

Évaluation des services communautaires pour les aînées et aînés d’expression anglaise de Gaspésie-îles-de-la-Madeleine - Richardson, Mary (2019)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Language related difficulties experienced by caregivers of English-speaking seniors in Quebec - Sanderson, Duncan (SAGE Open, 2020)
Little research has examined communication problems between speakers of official minority languages (patients or caregivers) and health care providers. The objective of this research was to identify the types of issues experienced by English-speaking caregivers of seniors in Quebec, as they interact with French-speaking health care providers. The majority of the caregivers interviewed indicated that they were satisfied with physicians’ interaction with the seniors they cared for. However, problems included health care providers who do not or who refuse to speak English, hospice personnel with insufficient English, anxiety about speaking to personnel in French, traveling to receive services in English, acting as an informal interpreter, receiving written documents in French, scheduling appointments through French-only phone systems or receptionists, and discrimination. The main finding is that in Quebec, language asymmetry might create additional stresses for an English-speaking caregiver, who is already likely to be stressed because of their caregiver role.

Prolonged Impact of the COVID-19 Pandemic on the Well-being and Roles of Family/Friend Caregivers of Older Adults Living at Home in Canadian Official Language Minority or Majority Communities - Savard, Jacinthe; Savard, Sébastien; Duong, Patrick; Hatungimana, Nelly Oriane; Benoit, Josée; De Moissac, Danielle; Dupuis-Blanchard, Suzanne; Robitaille, Annie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2026)
Résumé Contexte. Des études menées pendant la pandémie de COVID-19 soulignent que le confinement a réduit l’accès aux services et accru les responsabilités et l’isolement des proches aidants. Objectif. Cette étude examine les répercussions à long terme chez 83 proches aidants de personnes âgées provenant de quatre provinces canadiennes. Méthodes. Les participants ont rempli un questionnaire en ligne entre octobre 2021 et février 2022, puis à nouveau six mois plus tard, sur l’aide fournie, le soutien reçu, la langue des services et le bien-être psychologique. De plus, huit aidants ont participé à une entrevue qualitative. Résultats. La plupart des services d’aide à domicile ont été maintenus pendant la pandémie, certains avec un personnel réduit, à l’exception des services de répit et de transport. Les aidants ont accru leur aide pendant les confinements, et cette implication accrue s’est poursuivie en 2022. Ils ont perçu un impact négatif de la pandémie sur leur santé et celle de la personne aidée. Les participants issus de communautés linguistiques minoritaires officielles ont décrit des difficultés supplémentaires pour accéder aux services dans leur langue préférée. Discussion. Une meilleure reconnaissance des besoins des aidants contribuera à soutenir leur rôle en tant que partenaires au sein des organismes de santé. Abstract Background. Studies conducted during the COVID-19 pandemic highlighted that confinement reduced access to services and increased caregivers’ responsibilities and isolation. Objectives. This study examines the longer-term impacts among 83 unpaid caregivers of older adults from four Canadian provinces. Methods. Participants completed an online questionnaire between October 2021 and February 2022, and again 6 months later, on the assistance provided, support received, language of services, and psychological well-being. Additionally, eight caregivers participated in a qualitative interview. Findings. Most home support services were maintained during the pandemic – some with restricted staffing – except for respite and transportation services. Caregivers increased their assistance during the lockdowns, and this higher involvement persisted in 2022. They perceived a negative impact of the pandemic on their health and that of the care recipient. Participants from official language minority communities described additional challenges accessing services in their preferred language. Discussion. Greater recognition of caregivers’ needs will help support their role as partners within health organizations.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Culture, language and self- assesments of future health: Anglophones and Francophones in Quebec’s Eastern Townships - Stout, Dale; Charpentier, Claude; Chiasson, Myriam; Filion, Emmalie (Journal of Eastern Townships Studies, 2009)
This study examines subjective ratings of health (SRH) by Francophones and Anglophones living in the Eastern Townships. Global self-ratings of health are regarded as sensitive predictors of future health states, mortality, functional decline and disability, and utilization of the health-care system. Yet despite their pragmatic value, SRH are poorly understood. Along with a spontaneous monitoring of present health states, culture and language are listed as determinants of SRH. Few studies exist, however, that clearly delineate the direction and degree of effect that culture and language have on SRH. Adopting a temporal assessment of SRH, we asked 358 Anglophones (N=176) and Francophones (N=171) from the Eastern Townships, aged 18 to 95, to rate their health in the past, present, and future. To isolate culture and language effects we also asked participants to rate their future health if they “remained in Quebec”. Results revealed a significant interaction between age and temporal ratings of health (SRH). Turning to the effects of location (unspecified or “in Quebec”) on future health ratings, there was a significant interaction with language. Post hoc tests revealed no significant differences in Francophones’ future health ratings (unspecified or “in Quebec”) but a significant ratings drop was noted for Anglophones if they “remained in Quebec”. After controlling for bilingualism, this interaction remained statistically significant.

The effects of age and culture on subjective well-being: A case study in the Eastern Townships - Stout, Dale; Filion, Emmalie; Chiasson, Myriam; de Man, Anton; Charpentier, Claude; Pope, Megan (Journal of Eastern Townships Studies, 2008)
The present study of diachronous ratings of subjective well-being (SWB) was modeled on research undertaken by Staudinger, Bluck & Herzberg (2003). In addition, we were interested in determining the effects of culture and context (where one lives) on SWB ratings. To gage these effects, we included the factor of mother tongue and altered the Life Satisfaction Questionnaire by adding a question concerning expected well-being in Quebec. We asked 350 Anglophones and Francophones from the Eastern Townships, aged 18 to 95, to rate their SWB in the past, present, future, and future ‘in Quebec’. The results concerning the effects of chronological age on diachronistic SWB ratings followed the patterns of previous research: young people (aged 18–38) rate past SWB lower than present SWB and future SWB much higher; middle-aged people (aged 39–64) rate their SWB the same regardless of time; And the elderly (67–95) rated past SWB higher than the present and their future SWB much lower. There were no differences between Anglophones or Francophones. Further analysis revealed the disturbing finding that the oldest participants rated their current SWB significantly lower than the other two age groups. In the second half of our study we found that by simply asking Francophones and Anglophones to rate their SWB in the future – first unspecified as to location, and then in a future ‘if they stay in Quebec’ – produced different response patterns. Both future SWB ratings were the same for Francophones, indicating that the questions were simply redundant. The Anglophones, on the other hand, rated their future SWB in Quebec consistently lower than an unspecified future.

Access to health care services: East-End Montreal (Quebec) English-speaking elderly experience [master's thesis, McGill University] - Thomas, Rosemary Hellen. (2008)

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Language barriers to healthcare for linguistic minorities: The case of second language-specific health communication anxiety - Zhao, Yue; Segalowitz, Norman; Voloshyn, A.nastasiya; Chamoux, Estelle; Ryder, Andrew G. (Health Communication, 2021)
In this study we examined health communication anxiety (HCA) associated with language-discordant situations – that is, where people have to use their second language (L2) to communicate with health providers who are using their first language (L1). We adapted existing HCA scales in order to (1) assess L2 HCA in such situations separately for physical and mental/emotional health contexts and (2) control for potential confounds, such as HCA not related to L2 use and L2 communication anxiety not related to health, allowing us to obtain L2-specific measures of HCA. We examined the relationship between L2-specific HCA and willingness to use health services in language-discordant situations. English-speaking linguistic minority participants (N = 314) living in Québec, a predominantly French-speaking area of Canada, were recruited for online testing. The results revealed that, separately for both physical and mental/emotional health contexts, there were significant and meaningful L2-specific relations between HCA and willingness to use L2 health services – i.e., over and above general anxiety and discomfort about using an L2, and over and above general health communication anxiety. The effect was stronger for mental/emotional health contexts. The results are discussed in terms of their implications for understanding barriers to health services for linguistic minorities.